Acute spontaneous subdural hematoma: A literature review (Research, Society and Development, 2023)
Introduction: Cases of acute subdural hematomas are considered medical emergencies that should be treated with maximum urgency and efficacy. One class of this type of brain bleeding is spontaneous, classified mainly by the absence of trauma history and with distinct etiologies. Objective: This study aimed to evaluate the clinical, epidemiological and pathophysiological aspects of spontaneous acute subdural hematoma, basing the construction of knowledge on case reports. Materials and Methods: This is an integrative literature review about the general clinical features of spontaneous acute subdural hematoma. The PICO strategy was used to develop the guiding question. Furthermore, the descriptors "Acute Subdural Hematoma"; "Spontaneous Subdural Hematoma"; "Cerebral Hemorrhage" were cross-referenced with the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: A significant portion of the articles showed that the spontaneous acute subdural hematoma is caused by etiologies different from the traumatic cause, showing a difference in the precipitating factor, but keeping the typical clinical picture of subdural bleeding. Conclusion: It was possible to realize that spontaneous acute subdural hematoma is a modality of subdural bleeding, but it is precipitated by non-traumatic causes, such as arteriovenous malformations and rupture of aneurysms by hypertensive peaks. The prognosis is reserved, given its dependence on the site of involvement, as well as on the management adopted for the patient.